Analisis Stabilitas Tanggul Sungai Tondano, Kab. Minahasa, Sulawesi Utara - Ilham, Ilham; Muktadir, Redho; Taqwa, Fadhila Muhammad Libasut (Universitas Ibn Khaldun, 2026)
The Tondano River embankment serves a critical function in safeguarding residential areas and agricultural lands in Minahasa Regency against flood risks. However, according to data from the Regional Disaster Management Agency (2022), approximately 30% of the embankment segments have exhibited structural distress, including longitudinal cracking and subsidence, primarily triggered by internal seepage and toe erosion on the downstream slopes. This study evaluates the structural stability of the embankment at six critical cross-sections (P54, P78, CP7, P126, CP24, and P170) utilizing GEO5 2022 software, employing both the Spencer and Morgenstern-Price limit equilibrium methods. The analytical results indicate that under existing conditions, several sections failed to meet the minimum required safety factor (SF < 1.5), with critical values falling as low as 0.67 at CP7 and 0.76 at P126. While the implementation of Type III-n sheet piles with a 12-meter penetration depth was modeled at P54 and P126, the resulting deformations exceeded the structural capacity, necessitating the integration of gabion structures to provide additional passive resistance. This combined reinforcement strategy successfully increased the safety factor to 1.91 for P54 and 1.86 for P126. Based on these findings, the study proposes three distinct design classifications: Type 1 (integrated sheet pile and gabion system), Type 2 (stand-alone sheet pile), and Type 3 (unreinforced). Additionally, the installation of riprap protection is highly recommended across all downstream slopes to mitigate long-term erosive effects.